The Eloquence of Abu Bakr al-Siddiq’s Discourse: His Inaugural Caliphate Sermon as a Model (An Analytical Study) - Ayyash, Jamil Hussein (Journal of Arabic Language Sciences and Literature, 2025)
This paper presents a critical rhetorical analysis of the sermon delivered by Abu Bakr al-Siddiq (may Allah be pleased with him) upon his accession to the caliphate, treating it as a paradigmatic example of early Islamic political and religious oratory. The importance of this sermon lies not only in the critical historical circumstances under which it was delivered, but also in its profound thematic content, which demonstrates al-Siddiq’s acute awareness of the burdens of leadership and his unwavering commitment to the welfare of the Muslim community. The study is structured around three central dimensions. First, it examines Abu Bakr’s rhetorical mastery and his profound engagement with the Qur’an, particularly in his strategic employment of its meanings within his discourse. Second, it analyzes two representative passages from his statements, revealing their intellectual and ethical implications. Third, it investigates the rhetorical and stylistic devices employed in his inaugural address, emphasizing their role in reinforcing both the persuasive and moral dimensions of his speech. The findings reveal that Abu Bakr’s sermon exemplifies a unique synthesis of Arabic eloquence and just political leadership. It is distinguished by its precision of expression, depth of meaning, and equilibrium between rational argumentation and emotional appeal. Accordingly, it serves as a foundational reference for understanding the formative stages of Islamic oratory and its role in directing the Muslim community while embedding the values of justice, security, and social cohesion.